After the Affordable Care Act: Health Reform and the Safety Net. Issue 4 (2016) - Shin, Peter; Regenstein, Marsha
Abstract : Two major safety net providers – community health centers and public hospitals – continue to play a key role in the health care system even in the wake of coverage reform. This article examines the gains and threats they face under the Affordable Care Act.